A 2D Seismic Reflection and Interpretation Study of the Khan Al-Baghdadi area within the Palaeozoic Era (western Iraq) - Abdullah, Ali M.; Al-Rahim, Ali M.; Jassem, Kanaan A. (Iraqi Journal of Science, 2021)
This research deals with a 2D seismic structural and stratigraphic interpretation of Khan Al-Baghdadi area which is located in the western part of Iraq in Anbar governorate. Two main seismic reflectors are identified within the Silurian and Ordovician; these are the Hot_shale_1 within Akkas Formation and the Top Khabour Formation, which were deposited during the Paleozoic, based on synthetic seismogram of Akk_3 well near the study area. Time, depth, and velocity maps show the presence of two anticline structures trending east-west and located on the west side of the study area. The first is the Tulul structure (here denoted as A) and the second is denoted as B. Also, the maps show the increase in time towards the eastern side of the study area. The general slope of the reflectors is towards the southeast and the increase in the thickness of formations is gradually to the southwest and the northwest sides of the study area. The direct hydrocarbon indicator (DHI) was identified as sand lenses and flat spots on the studied reflectors, when applying seismic attributes like the instantaneous phase and the instantaneous Frequency), which give indicators of potential hydrocarbon accumulations. The primary reservoir in the study area is sandstone within the Khabour Formation, while the source and seal rocks are in the Hot_shale within Akkas Formation. They are interpreted to be present throughout Akkas Field, as gas-condensate accumulations, 100 km to the west of the study area and demonstrate the viability of the Paleozoic petroleum system in the Western Desert of Iraq.